mRNA-COVID19 Vaccination Can Be Considered Safe and Tolerable for Frail Patients - Lupo-Stanghellini, Maria Teresa; Di Cosimo, Serena; Costantini, Massimo; Monti, Sara; Mantegazza, Renato; Mantovani, Alberto; Salvarani, Carlo; Zinzani, Pier Luigi; Inglese, Matilde; Ciceri, Fabio; Apolone, Giovanni; Ciliberto, Gennaro; et al. (Frontiers in Oncology, 2022)
Frail patients are considered at relevant risk of complications due to COVID-19 infection. As these patients were originally not included in the registration trials, fear related to vaccine side-effects and disease worsening was one of the reasons for vaccine hesitancy. Herein we report the safety profile of the prospective, multicenter, national VAX4FRAIL study (NCT04848493) to evaluate vaccines in a large trans-disease cohort of patients with solid or hematological malignancies, neurological and rheumatological diseases. Between March 3rd and September 2nd, 2021, 566 patients were evaluable for safety endpoint: 105 received the mRNA-1273 vaccine and 461 the BNT162b2 vaccine. Frail patients were defined per protocol as patients under treatment with hematological malignancies (131), solid tumors (191), immune-rheumatological diseases (86), and neurological diseases (158), including multiple sclerosis and generalized myasthenia. The impact of the vaccination on the health status of patients was assessed through a questionnaire focused on the first week after each vaccine dose. The most frequently reported moderate-severe adverse events were pain at the injection site (60.3% after the first dose, 55.4% after the second), fatigue (30.1% - 41.7%), bone pain (27.4% - 27.2%) and headache (11.8% - 18.9%). Risk factors associated with the occurrence of severe symptoms after vaccine administration were identified through a multivariate logistic regression analysis: age was associated with severe fever presentation (younger patients vs. middle-aged vs. older ones), females presented a higher probability of severe pain at the injection site, fatigue, headache, and bone pain; the mRNA-1237 vaccine was associated with a higher probability of severe pain at the injection site and fever. After the first dose, patients presenting a severe symptom were at a relevant risk of recurrence of the same severe symptom after the second one. Overall, 11 patients (1.9%) after the first dose and 7 (1.2%) after the second one required to postpone or suspend the disease-specific treatment. Finally, 2 fatal events occurred among our 566 patients. These two events were considered unrelated to the vaccine. Our study reports that mRNA-COVID-19 vaccination is safe also in frail patients as expected side effects were manageable and had a minimum impact on patient care path.